2020
DOI: 10.1186/s12935-020-01663-4
|View full text |Cite
|
Sign up to set email alerts
|

CD44 cross-linking increases malignancy of breast cancer via upregulation of p-Moesin

Abstract: Background CD44 is highly expressed in most cancer cells and its cross-linking pattern is closely related to tumor migration and invasion. However, the underlying molecular mechanism regarding CD44 cross-linking during cancer cell metastasis is poorly understood. Therefore, the purpose of this study was to explore whether disruption of CD44 cross-linking in breast cancer cells could prevent the cells migration and invasion and determine the effects of CD44 cross-linking on the malignancy of the cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In the MDA-MB-231 cell line, but not the MCF-7 cell line, ANKHD1 silencing decreased cell migration (p < .05; Figure 3e). This result also highlighted the lower migratory capacity of MCF-7 compared to MDA-MB-231 cells, as previously reported (Hu et al, 2020).…”
Section: Ankhd1 Silencing Decreases Viability Clonogenicity and Migra...supporting
confidence: 88%
“…In the MDA-MB-231 cell line, but not the MCF-7 cell line, ANKHD1 silencing decreased cell migration (p < .05; Figure 3e). This result also highlighted the lower migratory capacity of MCF-7 compared to MDA-MB-231 cells, as previously reported (Hu et al, 2020).…”
Section: Ankhd1 Silencing Decreases Viability Clonogenicity and Migra...supporting
confidence: 88%
“…One recent study showed that via upregulation of p-moesin, CD44 cross-linking increases the malignancy of breast cancer. Moesin knockdown attenuated the promoting effect of CD44 cross-linking on tumor cell invasion and metastasis (55). Recently, Luo et al (56) proposed a novel mechanism of MSN contributing to tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Moesin functions as a potential oncogene in breast cancer by promoting cancer initiation, progression, and metastasis [ 6 , 27 29 ]. Further, it was found that Moesin is highly expressed in hormone receptor positive as well as negative breast cancer patients and its high-level expression is closely associated with poor prognosis [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was reported that suppression of NF-κB can result in serious host toxicity with minimum effect on the tumor [ 38 ] and therefore p65 is not an established cancer marker to develop therapeutic drugs. On the other hand, irrespective of hormone expression status, Moesin is known to be involved in breast cancer progression and metastasis [ 6 , 27 29 , 39 43 ] and is highly expressed in breast cancer [ 28 30 , 39 , 44 46 ]. Therefore, limiting Moesin expression level in breast cancer could be beneficial for the management of cancer progression.…”
Section: Discussionmentioning
confidence: 99%